Aortic and pulmonary artery dilatation in Cantu syndrome: expanding the phenotype. Issue 3 (July 2019) - Chew, Yi-Rong; Lim, Jiin-Ying; Teoh, Oon-Hoe; Chen, Ching-Kit; Foo, Roger; Lai, Angeline HM; Jamuar, Saumya S.
Abstract : Supplemental Digital Content is available in the text.